Food inequality in Kharkiv during the war: an overview of causes, manifestations and ways to overcome - Boiko Dmytro; Usenko Diana (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2023)
The article presents one of the aspects of the working theme of the Kharkiv team of the Fusilli project, namely, a general overview of the concept and phenomenon of food inequality as one of the forms of manifestation of general social inequality, as a process that outlines unequal and uneven access for different groups in different periods of time to benefits and resources necessary for the full reproduction of vital forces and provision of opportunities for personal development. Food inequality is problematized as a concept necessary to describe and explain the state of the city of Kharkiv under the conditions of a full-scale invasion at three stages: (1) the availability of food products as such in the Kharkiv region; (2) access to goods, that is, the very possibility of purchasing goods in one or another quantity and quality; (3) use of the goods, which are related to the possibility of consumption of the necessary goods. The concept and phenomenon of food inequality is correlated with other forms of social inequality, and an instrumental definition of the main causes and manifestations of food inequality is proposed. A general assessment of the state of food inequality in Ukraine is given and preliminary results of the author's sociological research are given. The article also reviews international, national and local initiatives aimed at solving the problem of food inequality, in particular the policies of central and local authorities, grant programs from foreign companies, the activities of local and international public, volunteer and charitable organizations. The authors come to the conclusion that the possibilities of solving the problem of food security exclusively by economic means and tools are limited, since it is a complex problem that requires a systematic solution involving not only economic, but also political, ecological, cultural, informational, etc. levers.